Psychologycal Well-being Pada Perempuan yang Mengalami Infertilitas Sekunder - Widia Sri Ardias; Bakhtiar Bakhtiar; Mela Purnama Gustia (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to determine the factors that influence psychological well-being on women who experience secondary infertility which can be seen from the dimensions of psychological well-being. This study also wants to illustrate how psychological well-being of women experiencing secondary infertility. The research method used is a qualitative descriptive method by collecting data through observation and interview techniques. Data analysis techniques with data reduction and categorization, making a description of the data, and then drawing conclusions. The data validity test through the extension of observation, increases the perseverance of triangulation. The results found first, the factors that influence psychological well-being in women who experience secondary infertility are age, social support from the surrounding environment and religiosity factors. Second, there are two dimensions of psychological well-being, namely negative feeling uncomfortable with other people's attitudes toward themselves and positive self-reliance on good personal growth, easy to get along and have a good life purpose.